Chemical evaluation and In-vitro gas emission in mixed King Grass and Clitoria-ternatea silages - López-Garrido, Serafín Jacobo; Ramos-Ramos , Diego Arturo; Galicia-Jiménez, Mónica Marcela; Camacho-Escobar, Marco Antonio; Ávila-Serrano, Narciso Ysac; Ramirez-Bribiesca, J. Efren (Ecosistemas y Recursos Agropecuarios, 2022)
The study evaluated the chemical composition, dry matter degradability, methane (CH4) and carbon dioxide (CO2) production in mixed silage. Micro silos of King grass CT-115 were made with the inclusion of 20, 30 and 40% of Clitoria ternatea adding 5.0% molasses and 0.5% phosphoric acid. After 40 days of fermentation, dry matter (DM), crude protein (PC), neutral detergent fiber (NDF), acid detergent fiber (ADF), pH, ammonia nitrogen (NA) and volatile fatty acids (VFA) were determined. The in vitro fermentation carried out measured dry matter degradability, CH4 and CO2 emissions at 24, 48 and 72h. The inclusion of Clitoria ternatea in the silages increased the content of DM and PC (P<0.05) and decreased (P<0.05) the percentages of NDF and FDA. The pH was less than 4.5 (P<0.05) with the addition of phosphoric acid. The VFA and NA concentrations indicated good quality of the silage. The inclusion of 40% of Clitoria ternatea in the silage produced a decrease of 27% of CH4 (P<0.05) during in vitro fermentation. In conclusion, the inclusion of 40% of Clitoria ternatea in King grass CT-115 silages improves the chemical composition and reduces CH4 emissions during in vitro ruminal fermentation.